Synthesis and Characterization of a Biomimetic Formulation of Clofazimine Hydrochloride Microcrystals for Parenteral Administration - Mikhail D. Murashov; Jennifer Diaz-Espinosa; Vernon LaLone; Joel W. Y. Tan; Raluca Laza; Xueding Wang; Kathleen A. Stringer; Gus R. Rosania (MDPI AG, 2018)
Clofazimine (CFZ) is a broad spectrum antimycobacterial agent recommended by the World Health Organization as a first line treatment for leprosy and second line treatment for multidrug resistant tuberculosis. Oral administration of CFZ leads to a red skin pigmentation side effect. Since CFZ is a weakly basic, red phenazine dye, the skin pigmentation side effect results from lipophilic partitioning of the circulating, free base (neutral) form of CFZ into the skin. Here, we developed a stable and biocompatible formulation of CFZ-HCl microcrystals that mimics the predominant form of the drug that bioaccumulates in macrophages, following long term oral CFZ administration. In mice, intravenous injection of these biomimetic CFZ-HCl microcrystals led to visible drug accumulation in macrophages of the reticuloendothelial system with minimal skin accumulation or pigmentation. In fact, no skin pigmentation was observed when the total amount of CFZ-HCl administered was equivalent to the total oral dose leading to maximal skin pigmentation. Thus, parenteral (injected or inhaled) biomimetic formulations of CFZ-HCl could be instrumental to avoid the pigmentation side effect of oral CFZ therapy.